Randomised controlled trial conducted in injecting equipment provision sites to compare the effectiveness of different hepatitis C treatment regimens in people who inject drugs: A Direct obserVed therApy versus fortNightly CollEction study for HCV treatment—ADVANCE HCV protocol study. Issue 8 (8th August 2019) - Inglis, Sarah K; Beer, Lewis JZ; Byrne, Christopher; Malaguti, Amy; Robinson, Emma; Sharkey, Christian; Gillings, Kirsty; Stephens, Brian; Dillon, John F
Abstract : Introduction: Hepatitis C is a blood-borne virus (HCV) that can seriously damage the liver and is spread mainly through blood-to-blood contact with an infected person. Over 85% of individuals who have HCV in Scotland became infected following injecting drug use. Since people who inject drugs (PWID) are the main source of new infections, theoretical modelling has suggested that treatment of HCV infection in PWID may effectively reduce HCV prevalence and accomplish elimination. This protocol describes a clinical trial delivering HCV treatment within injecting equipment provision sites (IEPS) in Tayside, Scotland. Methods and analysis: PWID attending IEPS are tested for HCV and, if they are chronically infected with HCV and eligible, invited to receive treatment within the IEPS. They are randomised to one of three treatment regimens; daily observed treatment, treatment dispensed every 2 weeks and treatment dispensed every 2 weeks together with an adherence psychological intervention (administered before treatment begins). The primary outcome is comparison of the rate of successful treatment (SVR12 ) in each treatment group. Secondary analyses include assessment of adherence, reinfection rates, viral resistance to treatment and interaction of the treatment with illicit drugs. Ethics and dissemination: The ADVANCE (A Direct obserVed therApy versus fortNightly CollEction) HCV trial was given favourable opinion by East of Scotland Research Ethics Committee (LR/17/ES/0089) prior to commencement. Trial registration numbers: European Clinical Trials Database (EudraCT) (2017-001039-38) and ClinicalTrials.gov (NCT03236506 ).